Language Literacy and Awereness Training on Code Switching with Appropriate Language Varieties According to the Context - Sisi Rosida; Leni Marlina (Raskha Media Group, 2026)
The phenomenon of code-switching that occurs massively and almost unnoticed among students of SMKS SPP Snakma Muhammadiyah. Low sociolinguistic awareness of students, stigma against code-switching as an indication of language failure, the absence of a structured intervention program. This program aims to improve students' understanding of code-switching as a functional language feature, foster sociolinguistic awareness in choosing appropriate language varieties according to context, and strengthen students' confidence in their multilingual identity. Activities are implemented through a participatory and contextual approach that includes three main stages, namely the preparation stage (coordination with partners, student needs survey, preparation of training modules, and development of evaluation instruments), the implementation stage, (delivery of conceptual material and mentoring in small groups, as well as discussions and providing feedback), and the evaluation and follow-up stage. The results of the activities show an increase in the average student understanding accompanied by positive changes in attitudes in the form of growing student confidence in choosing language varieties consciously and appropriately in context, both in writing and speaking practices. Thus, this program increases students' language awareness and has the potential to be replicated sustainably through the integration of training modules into language literacy activities in partner schools.